Mechanical and optical properties of MgAl2O4 ceramics and ballistic efficiency of spinel based armour. Issue 13 (1st July 2022) - Gajdowski, Caroline; D'Elia, Raffaele; Faderl, Norbert; Böhmler, Judith; Lorgouilloux, Yannick; Lemonnier, Sébastien; Leriche, Anne
Abstract: This study was devoted to the understanding of the influence of MgAl2 O4 ceramic properties on their ballistic performances. By modifying the processing parameters, ceramics with different microstructures were obtained. Among them, a transparent MgAl2 O4 spinel with an in-line transmission between 77% and 83% in the visible range, an average grain size of 8.6 μm and good mechanical properties (11.3 GPa in Knoop hardness and 2.5 MPa√m in fracture toughness) was produced. A thorough characterisation of the ceramics was accomplished in order to establish a link between microstructure, mechanical properties and ballistic protective performances against an armour piercing projectile of calibre 7.62x51 mm. The ballistic evaluation demonstrated the advantage of using a spinel layer as the strike face to stop a threat, while reducing drastically the thickness and the areal density of the transparent multilayer, compared to a simple glass armour. MgAl2 O4 spinel with fine grains presented a better combination of mechanical properties compared to coarser microstructures, hence a better potential to damage a projectile at the impact.